Math Formula--General Term
posted by Anonymous .
Consider the sequence 12, 5, -2, -9
Determine the formula for the general term of the sequence:
tn = a + (n-1)d
tn = 12 + (n-1)-7
tn = 12-7n + 7
tn = -7n + 19
I got -7n +19 as the answer, but at the back of the book, it says.. tn = 19-7n. I have no idea how the numbers got mixed up :\
Both are correct, and mathematically equivalent.
A linear expression is usually presented the way you did, i.e. the term with the variable first, followed by the constant:
However, there are times that we want to get rid of the annoying leading negative sign (if there are positive terms), and place the positive term first.